Targeting heme degradation pathway augments prostate cancer cell sensitivity to docetaxel-induced apoptosis and attenuates migration - Salloom, Ramia J.; Ahmad, Iman M.; Abdalla, Maher Y. (Frontiers in Oncology, 2024)
Chemotherapy, notably docetaxel (Doc), stands as the primary treatment for castration-resistant prostate cancer (CRPC). However, its efficacy is hindered by side effects and chemoresistance. Hypoxia in prostate cancer (PC) correlates with chemoresistance to Doc-induced apoptosis via Heme Oxygenase-1 (HO-1) modulation, a key enzyme in heme metabolism. This study investigated targeting heme degradation pathway via HO-1 inhibition to potentiate the therapeutic efficacy of Doc in PC. Utilizing diverse PC cell lines, we evaluated HO-1 inhibition alone and with Doc on viability, apoptosis, migration, and epithelial-to-mesenchymal transition (EMT) markers and elucidated the underlying mechanisms. HO-1 inhibition significantly reduced PC cell viability under hypoxic and normoxic conditions, enhancing Doc-induced apoptosis through interconnected mechanisms, including elevated reactive oxygen species (ROS) levels, glutathione cycle disruption, and modulation of Signal Transducer and Activator of Transcription 1 (STAT1) pathway. The interplay between STAT1 and HO-1 suggests its reliance on HO-1 activation. Additionally, a decrease in cell migration and downregulation of EMT markers (vimentin and snail) were observed, indicating attenuation of mesenchymal phenotype. In conclusion, the combination of HO-1 inhibition with Doc holds promise for improving therapeutic outcomes and advancing clinical management in PC.